Positive Youth Development and Wellbeing: Gender Differences - Tomé, Gina; Gaspar de Matos, Margarida; Reis, Marta; Gomez-Baya, Diego; Coelhoso, Filipa; Wiium, Nora (Frontiers in Psychology, 2021)
The five C’s of positive youth development (PYD) (competence, confidence, character, caring, and connection) have been associated with adaptive development among young people. Gender differences in young people’s wellbeing and mental health have been studied and analyzed, but the investigation into their association with the five C’s is still in its infancy. In the present study, we analyzed the influence of the five C’s on the wellbeing, more specifically, anxiety, social alienation, general wellbeing, physical symptoms, and psychological symptoms, of Portuguese adolescents, by gender. Participants were 5th–12th grade students attending public schools in Lisbon, Portugal. The questionnaire was administered to 384 adolescents. The results indicated important gender differences in young people’s wellbeing. The results revealed some differences between genders that should be considered in interventions that aim to promote the wellbeing of adolescents. On the other hand, confidence was positively associated with mental health and wellbeing for both boys and girls, skill should be promoted among young people, because it was competence that revealed the greatest association with wellbeing, among the variables analyzed.